Attraction and Retention of Talent in the Tourism Sector. Empirical Evidence in the South of Europe - Ruiz-Molina, Antonio; Jiménez-Quintero, José Antonio; Casado-Salguero, Gisela (Departamento de Turismo do ISCE (LISBOA - Portugal), 2013)
The effect that an increase on the workmanship’s quality in the tourism sector, has over the productivity increase, the improvement of living conditions and the economic growth is widely known. In this context, strategy in human resources, one of the key factors in achieving a competitive advantage, must be a stimulus to attract the most talented human capital and to develop its career in this sector, which will result in an improvement in the business performance expectations. The aim in this report is to obtain empirical evidence about the attraction and retention of the human capital with special abilities, in the Andalusian tourism sector (with special reference to Málaga and Granada), using educational disparity as a proxy. The methodology used in its analysis has been the statistical method, in the trend-based version, after categorizing the hotel establishments (in Málaga and Granada) using discriminating analysis of aggregate economic information most relevant to each enterprise. For the application of the statistical method, information from a survey done to hotel establishments and a Delphi analysis to experts and community leaders, have been used. The most relevant conclusion, in general terms, concerns the disparity between the assessment of the importance attached to the Human Resources Strategy and its development in practice. In this way, a dichotomy in the level of education can be perceived as an over-education problem, while at the same time formal training is insufficient for efficient performance at work.
www.isce-turismo.com
Keywords: Turismo - Gestión de personal; Human Resources Strategy; Retaining talent